Will and power: Investment diversification and systemic deviation from irrational risk - Yaping Liu (Cogent Economics & Finance, 2022)
Examining China's stock market, mean variance is used to measure returns and risk and build an irrational risk-asset pricing model. The power of heterogeneous beliefs and risk-valuation deviation are found to affect capital asset pricing, presenting excessive fluctuations that neoclassical finance theory cannot easily explain. A diversified portfolio can disperse or aggregate irrational risk. Trading frequency and quantity reflect differences in investors' rationality and reveal irrational risk effects. On that basis, regulatory tools and derivative products can be designed to build a rational risk anchor, prevent the systematic bias of irrational risk, and improve capital allocation.
Keywords: 330; behavioral finance; equity premium; Irrational risk; risk aggregation; risk-valuation deviation